1993
DOI: 10.1111/j.1600-051x.1993.tb01759.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a mouthrinse containing chlorhexidine and fluoride on plaque and gingival bleeding

Abstract: The aim of this study was to test the effect of a rinse with 0.05% sodium fluoride and 0.05% chlorhexidine on plaque and gingival inflammation compared with a placebo without these agents. In a double-blind study, 47 adults with > 20 teeth and a CPITN score > 1 but < 4 were randomised into test and control groups. After baseline assessments for plaque, bleeding and stain, teeth were professionally cleaned. Subjects were asked to rinse for 30 s with 10 ml of the respective test or placebo rinse after normal ora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 9 publications
1
13
0
1
Order By: Relevance
“…26 An important part of the mouthcare regimen for immunosuppressed patients is rinsing with 0.2% chlorhexidine, which if used effectively, reduces plaque accumulation (and bacterial loading). 27,28 This has been reported by several groups of investigators, [29][30][31] as has a reduction in the frequency of isolation of the viridans streptococci. 30,32 Most of the children in the present study were unable to use the chlorhexidine effectively for two main reasons.…”
Section: Discussionmentioning
confidence: 64%
“…26 An important part of the mouthcare regimen for immunosuppressed patients is rinsing with 0.2% chlorhexidine, which if used effectively, reduces plaque accumulation (and bacterial loading). 27,28 This has been reported by several groups of investigators, [29][30][31] as has a reduction in the frequency of isolation of the viridans streptococci. 30,32 Most of the children in the present study were unable to use the chlorhexidine effectively for two main reasons.…”
Section: Discussionmentioning
confidence: 64%
“…). Although the plaque inhibition of low CHX concentrations is dose‐dependent, and low‐concentration rinses may be less effective, some studies have demonstrated efficacy of low‐CHX rinses (0.06%) in reducing plaque (Joyston‐Bechal & Hernaman , Hoffmann et al. , Claydon et al.…”
Section: Discussionmentioning
confidence: 99%
“…Concentrations of 0.12% CHX appear to be as effective as 0.2% if the volume of the rinse is increased from 10 to 15 ml, each of which provides a dose of 18 mg (Keijser et al 2003, Van Strydonck et al 2005. Although the plaque inhibition of low CHX concentrations is dosedependent, and low-concentration rinses may be less effective, some studies have demonstrated efficacy of low-CHX rinses (0.06%) in reducing plaque (Joyston-Bechal & Hernaman 1993, Hoffmann et al 2001, Claydon et al 2002, Zimmer et al 2006, Duss et al 2010. The efficacy of low CHX concentrations on the reduction on gingival inflammation however remains unclear.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…Solutions of 0.2% CHX ‡, 0.05% CHX and 0.05% CPC were used. A concentration of 0.05% CPC was chosen as this is the most common concentration of CPC found in over‐the‐counter mouthwash preparations and has been a concentration used for some CHX mouthwashes ( Jenkins et al 1993, Joyston Bechal & Hernaman 1993). The 0.05% solution of CHX was prepared from a 20% aqueous solution † and distilled water.…”
Section: Methodsmentioning
confidence: 99%